Multiple functions of thymosin β4 in the pearl oyster Pinctada fucata suggest its multiple potential roles in artificial pearl culture. Issue 103 (August 2020) - Bai, Lirong; He, Wenyao; Fan, Sigang; Liu, Baosuo; Zhou, Tong; Zhang, Dongling; Zhang, Dianchang; Yu, Dahui
Abstract: Thymosin β4 is a multifunctional protein in vertebrates that participates in physiological processes, such as wound healing, immune response, cell proliferation and migration. We assessed the multifarious roles of this small peptide in Pinctada fucata, an oyster commonly used in pearl culture in China. Our results showed that when P. fucata was challenged by bacterial pathogens or LPS, the relative expression level of Pfthymosin β4 mRNA was significantly up-regulated, suggesting its involvement in immune response of the animal. Recombinant Pfthymosin β4 (rPfthymosin β4) was produced and showed in vitro different antibacterial activities against different pathogenic bacteria; the inhibitory effect of rPfthymosin β4 on bacterial growth was relatively stronger in the broth culture than agar culture. The overexpression of Pfthymosin β4 in Escherichia coli BL21(DE3) cells could improve their resistance to Cu 2+, Zn 2+, Cd 2+, and H2 O2, suggesting that Pfthymosin β4 is likely involved with antioxidant. rPfthymosin β4 also significantly promoted the proliferation and migration of mouse aortic vascular smooth muscle cells as indicated by MTT assay and cell scratch assay, respectively. In addition, chemically synthesized or recombinant Pfthymosin β4 could transiently increase the circulating total hemocytes counts but down-regulated by RNAi in P. fucata. Taking together above results and previous studies suggested that Pfthymosin β4 is potentially able to promote wound healing through enhancing antibacterial activity and antioxidant capacity, promotion of cell proliferation and migration, and increase of circulating hemocytes in P. fucata due to nucleus implantation injury. Thus, the future of recombinant Pfthymosin β4 should be promising in the culture of pearls in P. fucata . Highlights: Recombinant Pfthymosin β4 was prepared and used in different activity assays. It possessed antibacterial activity and enhanced antioxidative capacity of cells. Pfthymosin β4 was stimulated by different pathogens and immunostimulants. Pfthymosin β4 increased the number of circulating hemocytes. It can be used in pearl culture to prevent infection and to enhance the immunity.